x^{μ-1}/sinh^{2}ax[0,∞]などの定積分

\begin{alignat}{2}
&(1)  \displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\sinh^2 ax}dx=\frac{4}{(2a)^μ}ζ(μ-1)Γ(μ)  (μ \gt 2)\\
&(2)  \displaystyle\int_0^{\infty} \frac{x^{2n}}{\sinh^2 ax}dx=\frac{π^{2n}}{a^{2n+1}}|B_{2n}|\\
&(3)  \displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\cosh^2 ax}dx=\frac{4}{(2a)^μ}(1-2^{2-μ})ζ(μ-1)Γ(μ)  (μ\gt 0, μ≠2)\\
&(4)  \displaystyle\int_0^{\infty} \frac{x}{\cosh^2 ax}dx=\frac{\log 2}{a^2}\\
&(5)  \displaystyle\int_0^{\infty} \frac{x^{2n}}{\cosh^2 ax}dx=\frac{4(2^{2n-1}-1)π^{2n}}{(2a)^{2n+1}}|B_{2n}|\\
&(6)  \displaystyle\int_{-\infty}^{\infty} \frac{x^2}{\sinh^2 x}dx=\frac{π^2}{3}
\end{alignat}ただし、全て \(a \gt 0, n \in \mathrm{N}\)









<証明>

\begin{alignat}{2}
&(1) \displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\sinh^2 ax}dx=\displaystyle\int_0^{\infty} x^{μ-1} \cdot \frac{4}{(e^{ax}-e^{-ax})^2}dx\\
&                 =4\displaystyle\int_0^{\infty} x^{μ-1} \cdot \frac{e^{-2ax}}{(1-e^{-2ax})^2}dx\\
&                 =4 \displaystyle\int_0^{\infty} x^{μ-1}e^{-2ax}\displaystyle\sum_{n=1}^{\infty} ne^{-2(n-1)ax}dx\\
&                 =4 \displaystyle\sum_{n=1}^{\infty} n \displaystyle\int_0^{\infty }x^{μ-1}e^{-2nax}dx\\
\end{alignat}\(2nax=t\) と置きます。\((2nadx=dt)\)
\begin{alignat}{2}
&=4 \displaystyle\sum_{n=1}^{\infty} n \displaystyle\int_0^{\infty} \left(\frac{t}{2na}\right)^{μ-1}e^{-t} \cdot \frac{1}{2na}dt\\
&=\frac{4}{(2a)^μ}\displaystyle\sum_{n=1}^{\infty} \frac{1}{n^{μ-1}}\displaystyle\int_0^{\infty} t^{μ-1}e^{-t}dt=\frac{4}{(2a)^μ}ζ(μ-1)Γ(μ)
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\sinh^2 ax}dx=\frac{4}{(2a)^μ}ζ(μ-1)Γ(μ)$$







\((2)\) \((1)\) の式で \(μ=2n+1\) とします。
\begin{alignat}{2}
&\displaystyle\int_0^{\infty} \frac{x^{2n}}{\sinh^2 ax}dx=\frac{4}{(2a)^{2n+1}}ζ(2n)Γ(2n+1)\\
&             =\frac{4}{(2a)^{2n+1}} \cdot \frac{(2π)^{2n}|B_{2n}|}{2\cdot (2n)!} \cdot (2n)!=\frac{π^{2n}}{a^{2n+1}}|B_{2n}|
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{x^{2n}}{\sinh^2 ax}dx=\frac{π^{2n}}{a^{2n+1}}|B_{2n}|$$







\begin{alignat}{2}
&(3) \displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\cosh^2 ax}dx=\displaystyle\int_0^{\infty} x^{μ-1} \cdot \frac{4}{(e^{ax}+e^{-ax})^2}dx\\
&                 =4\displaystyle\int_0^{\infty} x^{μ-1} \cdot \frac{e^{-2ax}}{(1+e^{-2ax})^2}dx\\
&                 =4 \displaystyle\int_0^{\infty} x^{μ-1}e^{-2ax}\displaystyle\sum_{n=1}^{\infty} (-1)^{n-1}ne^{-2(n-1)ax}dx\\
&                 =4 \displaystyle\sum_{n=1}^{\infty} (-1)^{n-1}n \displaystyle\int_0^{\infty }x^{μ-1}e^{-2nax}dx\\
\end{alignat}\(2nax=t\) と置きます。\((2nadx=dt)\)
\begin{alignat}{2}
&=4 \displaystyle\sum_{n=1}^{\infty} (-1)^{n-1}n \displaystyle\int_0^{\infty} \left(\frac{t}{2na}\right)^{μ-1}e^{-t} \cdot \frac{1}{2na}dt\\
&=\frac{4}{(2a)^μ}\displaystyle\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{n^{μ-1}}\displaystyle\int_0^{\infty} t^{μ-1}e^{-t}dt\\
&=\frac{4}{(2a)^μ}η(μ-1)Γ(μ)=\frac{4}{(2a)^μ}(1-2^{2-μ})ζ(μ-1)Γ(μ)
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{x^{μ-1}}{\cosh^2 ax}dx=\frac{4}{(2a)^μ}(1-2^{2-μ})ζ(μ-1)Γ(μ)$$








\((4)\) \((3)\) の最後から \(2\) 番目の式で \(μ=2\) とします。$$\displaystyle\int_0^{\infty} \frac{x}{\cosh^2 ax}dx=\frac{4}{(2a)^2}η(1)Γ(2)=\frac{1}{a^2}\displaystyle\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{n}=\frac{\log 2}{a^2}$$







\((5)\) \((3)\) の式で \(μ=2n+1\) とします。
\begin{alignat}{2}
&\displaystyle\int_0^{\infty} \frac{x^{2n}}{\cosh^2 ax}dx=\frac{4}{(2a)^{2n+1}}(1-2^{1-2n})ζ(2n)Γ(2n+1)\\
&              =\frac{4}{(2a)^{2n+1}} \cdot \frac{2^{2n-1}-1}{2^{2n-1}}\cdot \frac{(2π)^{2n}|B_{2n}|}{2 \cdot (2n)!} \cdot (2n)!\\
&              =\frac{4(2^{2n-1}-1)π^{2n}}{(2a)^{2n+1}}|B_{2n}|
\end{alignat}以上より$$\displaystyle\int_0^{\infty} \frac{x^{2n}}{\cosh^2 ax}dx=\frac{4(2^{2n-1}-1)π^{2n}}{(2a)^{2n+1}}|B_{2n}|$$







\((6)\) \((1)\) の式で \(a=1, μ=3\) とします。$$\displaystyle\int_{-\infty}^{\infty} \frac{x^2}{\sinh^2 x}dx=2\displaystyle\int_0^{\infty} \frac{x^2}{\sinh^2 x}dx=2 \cdot \frac{4}{8}\cdot Γ(3)ζ(2)=2 \cdot \frac{π^2}{6}=\frac{π^2}{3}$$

コメントを残す

メールアドレスが公開されることはありません。 * が付いている欄は必須項目です